Penggunaan Aplikasi CERITA (Cermati Berita Bareng Yuanita) Berbasis Android Sebagai Media Pembelajaran Bahasa Indonesia yang Interaktif - Fitriyana, Yuanita; Nurhamidah, Didah (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The study aims to describe the development of a story application (a news closer together with yuanita) to help in text study. The story application (both yuanita and yuanita) based android that teaches about the news text. This research method involves qualitative methods. Angket for the research sample was 40 x graders at IP high school. The process of building a story application (both yuanita and yuanita together) is conducted on needs analysis based on link gfrom and direct debrief of the news text and results in which many of the respondents have not been able to know the correct use and execution of the news text. The story application (check the news together with yuanita) is excellent for use in helping to understand the text that has not been taught in school. The story application (sharing yuanita's news coverage) has been rated as able to become an innovative and expressive medium of learning to be taught at learning time.